IVS1 −397T>C Estrogen Receptor α Polymorphism Is Associated with Low-Grade Systemic Inflammatory Response in Type 1 Diabetic Girls - Monika Ryba-Stanisławowska; Karolina Rybarczyk-Kapturska; Agnieszka Brandt; Małgorzata Myśliwiec; Jolanta Myśliwska (Hindawi Limited, 2014)
Purpose. The study aimed to investigate the influence of estrogen receptor α (ER-α) genotypes on inflammatory response and development of microvascular complications in girls with type 1 diabetes. Methods. 152 young regularly menstruating girls with diagnosed type 1 diabetes and 84 young, healthy menstruating girls were recruited. ER-α genotyping was carried out by PCR. Serum concentrations of 17β-estradiol, as well as IL-6, TNF-α, VEGF, and IL-10, were measured. CD4+Foxp3+ TH17 cells were isolated and analyzed by flow cytometry. Results. Type 1 diabetic girls carrying TT genotype were characterized by the lowest serum estradiol level and IL-10 and highest IL-6, TNF-α , and VEGF. The association between the level of certain cytokine and the genetic variant of estrogen receptor α polymorphism was analyzed. Frequencies of CD4+Foxp3+ TH17 cells were also enhanced in TT bearing girls with type 1 diabetes and correlated with the level of analyzed cytokines. In addition, the correlation between serum estradiol level and cytokine concentrations was observed. Conclusions. We propose that TT variant of estrogen receptor α polymorphism may be associated with enhanced inflammatory response, which in turn may lead to acceleration of diabetic retino- and nephropathy in girls with type 1 diabetes. This finding may help the physicians to predict the onset and progression of diabetic microvascular complications.